Working from home and job satisfaction: The role of gender and personality traits - P. Esposito; S. Mendolia; S. Scicchitano; C. Tealdi (Global Labor Organization (GLO), 2024)
In this paper we investigate the effect of working-from home (WFH) on job satisfaction. We use longitudinal data from Italy to estimate a difference-in-differences model, in which the treatment group includes individuals who transitioned to remote work in 2020 due to the COVID-19 pandemic and continued to work from home in 2021. We perform the analysis, which extends to various aspects of self-reported job satisfaction, by gender and personality traits as per the Big-Five framework, encompassing Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. Our findings reveal that WFH exhibits a positive influence on job satisfaction, albeit exclusively among women, and with some heterogeneity, depending on personal characteristics. Specifically, this effect seems more noticeable in women characterized by elevated Openness to Experience, whereas those with heightened conscientiousness or neuroticism levels tend to experience less satisfaction when working remotely.
Keywords: J28; J81; J16; 330; remote working; difference in differences; longitudinal analysis; gender differences; Big-Five framework